Service function chain deployment scheme based on heterogeneous backup and remapping - Jichao XIE; Peng YI; Zhen ZHANG; Chuanhao ZHANG; Yunjie GU (网络与信息安全学报)
Network function virtualization technology improves the flexibility of service function chains' deployment.However,the virtual network functions are under the pressure of uncertain failures and malicious attacks.The existing redundant backup methods can solve the problem of VNF failures to some extent,it does not consider the defects of node homogeneity in the face of malicious attacks.A deployment method considering the heterogeneity of nodes was proposed,guaranteeing the heterogeneity of nodes when perform redundant backup and remapping.Simulation experiments demonstrate that the proposed method significantly increases attacker's attack time cost under the cost of the request acceptance rate decreases by 3.8% and the bandwidth consumption increase by 9.2% comparing to the homogeneity backup method.